Model Praktik Perilaku Pengelolaan Keuangan Pranikah Pada Pasangan Siap Menikah Di Kota Medan - Wahyuni, Sri Fitri; Hafiz, Muhammad Shareza; Lestari, Sri Puji (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to examine the influence of financial literacy, income and lifestyle on financial management behavior among couples ready to get married in the city of Medan. The population in this study is all couples who are ready to marry in several districts in the city of Medan. To determine the sample using the Lemeshow formula because the population size is unknown, the researcher took the sample using the accidental sampling method, namely the sample was carried out by chance with 280 premarital couple respondents as the research sample. The data analysis techniques used in this research are measurement model analysis (outer model) and variance-based structural equation testing or better known as Partial Least Square (PLS) using Smart PLS 3.0 software. The results of this study indicate that financial literacy has a significant effect on financial management behavior. Income has no significant effect on Financial Management Behavior. Lifestyle has a significant influence on Financial Management Behavior